PRODUCING DESIGN: WHICH WAY? - Ashour, Ayman (PEOPLE: International Journal of Social Sciences, 2017)
This paper argues that the recent trend of encouraging creativity in design should be critically examined. The paper discusses “creating” vs. “making” as an intellectual exercise in the context of art and design production, where making is an action of the rational intellect and creating is an action of the will for originality. The paper concludes by offering suggestions that will prepare designers to recognize the differences between making and creating, hence the implications on art and design production. The studio of design is not the real practice world; masters may flourish outside of academic world, however, in the context of design education, instructors must help design students become competent before they can become independent. Students have to figure out how to make before they are required to create.